2016
DOI: 10.21009/jkkp.032.01
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Dukungan Keluarga Dalam Kemandirian Lansia Di Desa Payungsari Kecamatan Pedes Kabupaten Karawang

Abstract: Lansia (lanjut usia) adalah seseorang yang karena usianya mengalami perubahan biologis, fisik, kejiwaan   dan   sosial. Ukuran kemandirian lansia dapat dilihat dengan cara lansia melakukan aktifitasnya sendiri tanpa bantuan dari orang lain. Dukungan keluarga diperlukan untuk dapat menjadi fasilitator yang menjembatani antara lansia dengan lingkungan dan masyarakat. Penelitian ini bertujuan untuk mengetahui bagaimana dukungan keluarga dalam kemandirian lansia di desa Payungsari kecamatan Pedes kabupaten Karawan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Previous research found that the family has a significant and positive effect on the quality of elderly's life (Putri et al, 2019). This means that the functioning of the elderly to get family support will improve the quality life of the elderly(Al Munawaroh et al, 2016) Where they will feel happy and maximise their quality of life Mutual understanding of family members, based on the results of research with 5 pairs of informants about mutual understanding in a family obtained excellent results the primary informant is so understandable for the secondary informant, but the secondary informant always tries to communicate with the primary informant. This is similar to the theory presented by Gunarsa (2012).…”
Section: Harmonization Relationships In Elderly People Living Apart F...mentioning
confidence: 99%
“…Previous research found that the family has a significant and positive effect on the quality of elderly's life (Putri et al, 2019). This means that the functioning of the elderly to get family support will improve the quality life of the elderly(Al Munawaroh et al, 2016) Where they will feel happy and maximise their quality of life Mutual understanding of family members, based on the results of research with 5 pairs of informants about mutual understanding in a family obtained excellent results the primary informant is so understandable for the secondary informant, but the secondary informant always tries to communicate with the primary informant. This is similar to the theory presented by Gunarsa (2012).…”
Section: Harmonization Relationships In Elderly People Living Apart F...mentioning
confidence: 99%